Outgassing effect in polymeric composites exposed to space environment thermal-vacuum conditions. (May 2020) - Pastore, R.; Delfini, A.; Albano, M.; Vricella, A.; Marchetti, M.; Santoni, F.; Piergentili, F.
Abstract: Polymeric composites are widely adopted for design and realization of spacecraft components and subsystems, due to their lightweight and thermo-mechanical properties. However, the use of such materials for aerospace operations should be carefully conceived, since the detrimental effects they may experience within the severe space environment. A typical issue to be considered is represented by the outgassing phenomena a polymeric composite suffers in ultra-high vacuum at elevated temperatures: in this harsh condition, a release of gaseous species from the material surface takes place, resulting in structural depletion and nearby components contamination. The present work describes the results of outgassing tests carried out on three typologies of widely used polymeric composites, such as epoxy matrix reinforced by carbon fiber, fiberglass and aramid fabric. The experimental behavior of these materials is analyzed with the aid of infrared spectroscopy, in order to gain knowledge about the chemical modifications that outgassing dynamics induce on the fiber-intercalated polymeric chains. The compliance to space assurance requirements – i.e., mass loss and condensed matter amounts vs. standard outgassing rates thresholds – is discussed with regard to the different functionalities each material is envisaged to accomplish, when applied onto space vehicle's exposed side. Further, in case of exceeding outgassing rate, a pre-treatment by thermal conditioning is proposed to improve the chemical stability of materials in thermal-vacuum conditions, in order to explore the feasibility of their use for aerospace applications. Highlights: Evaluate composites outgassing is mandatory for aerospace missions. A facile low cost composites production route is proposed. Carbon fiber composite shows acceptable outgassing rates. Fiberglass and Kevlar composites should be screened. A novel outgassing dynamics modeling is introduced.